Desvendando a metodologia da animação clássica: a arte do desenho animado como empreendimento industrial - Antonio Cesar Fialho de Sousa (2005)
The present study aims to shed light upon the methodologicalprocess involved in the making of animated features. Regardless of itsreproduction format and media, the animation process comprises a sequence of fixed procedures which must be reflected upon by animators and directors alike so that they may, given budgetary limitations, oversee the projects' technical quality in an efficient manner, without compromising the creative process of the actual animation. This phase and its inherent methodology are central to this study, along with an attempt to elaborate a systemic view of the evolution of the animation studio as an entertainment industry business venture and its natureas an organized enterprise.It is as important that future chief animators in Brazil have an overview of the organizational structure in animation studios and their underlying artistic and functional hierarchy, as it is crucial that they identify andreflect upon the division of labor when forming an animation team to work in the production of an animated feature or any such project. This knowledge will help them to better assemble teams and lay down members functional responsibilities in order to meet production deadlines and guarantee technical and artistic quality, while fully understanding the dichotomy of the animated feature as a product of the Art Industry.